1989
DOI: 10.1111/j.1365-2125.1989.tb05340.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of oral activated charcoal on quinine elimination.

Abstract: The effect of repeated dose oral activated charcoal on quinine elimination has been studied following a therapeutic (600 mg) dose of quinine bisulphate to seven normal volunteers. Activated charcoal lowered quinine half‐life from 8.23 +/‐ 0.57 s.d. h to 4.55 +/‐ 0.15 s.d. h (P less than 0.001) and increased its oral clearance by 56%. Activated charcoal may have a role in the management of quinine poisoning.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

1989
1989
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(12 citation statements)
references
References 6 publications
1
11
0
Order By: Relevance
“…This has been demonstrated both in volunteers following a therapeutic dose of quinine bisulphate (Lockey & Bateman, 1989) and in patients following overdose where the mean half-life was 8.1 h compared with 24 h in a similar group of poisoned patients not given activated charcoal (Bateman et al, 1985b;Prescott et al, 1989). In one patient despite a 36-h delay between overdose and starting oral activated charcoal the half-life was reduced from 33h to 10h (Prescott et al, 1985).…”
Section: Discussionmentioning
confidence: 93%
“…This has been demonstrated both in volunteers following a therapeutic dose of quinine bisulphate (Lockey & Bateman, 1989) and in patients following overdose where the mean half-life was 8.1 h compared with 24 h in a similar group of poisoned patients not given activated charcoal (Bateman et al, 1985b;Prescott et al, 1989). In one patient despite a 36-h delay between overdose and starting oral activated charcoal the half-life was reduced from 33h to 10h (Prescott et al, 1985).…”
Section: Discussionmentioning
confidence: 93%
“…Although advocated in the past, urinary acidification has not been shown to reduce the elimination half‐life of quinine in poisoned patients and does not greatly enhance quinine removal 17 . Although extracorporeal methods of elimination have been previously used, they are ineffective at enhancing removal of quinine and are not recommended 17,27,28 .…”
Section: Discussionmentioning
confidence: 99%
“…• Studies in volunteers have demonstrated that multiple-dose activated charcoal increases the elimination of carbamazepine, 5 dapsone, 6 dextropropoxyphene, 7 digitoxin, 8,9 digoxin, 8-10 disopyramide, 11 nadolol, 12 phenobarbital, 5,13-15 phenylbutazone, 5 phenytoin, 16,17 piroxicam, 18 quinine, 19 sotalol, 20 and theophylline. [21][22][23][24][25][26] • The elimination of salicylate was increased by multiple-dose activated charcoal in two studies, 27,28 but not in two other studies.…”
Section: Volunteer Studiesmentioning
confidence: 99%
“…19 Activated charcoal 50 g was administered 4 hours after quinine dosing and 3 further doses were given over the next 12 hours. The effect of multiple-dose activated charcoal on quinine elimination was studied following a therapeutic (600 mg) dose of quinine bisulphate to 7 adult fasted volunteers.…”
Section: Reprintsmentioning
confidence: 99%